O PLANTIO DA PALMA DE ESPINHO Opuntia dillenii (ker-Grawl.) Haw. EM ROÇADOS DE ESPINHO NO SEMIÁRIDO PARAIBANO - Albuquerque, Alisson Santos de (2016)
Considering the multiplicity of uses; resistance to pests, diseases, drought; the high production per unit area and your rapid spread and the fact that the same is found in various regions within the Brazilian semi-arid region without characterizing as "weed". This work aimed to obtain phenological data of production and acclimatization of Palma de Espinho (Opuntia dillenii) in Brazilian semi-arid conditions. The study was developed in the community of San Pedro, located in the district of Boa Vista, Campina Grande-PB, Brazil, the planting was in pits/cots with 0.15 m depth with the rackets being planted diagonally lengthwise of your length. The spacing was 1.50 m x 0.50 m x 0.50 being planted five double lines of plants totaling 22 double 110 plants/plot, the area was not plowed or graded. The planting was in August 2015 and the collection of data in June 2016 resulting in 10 Months After Planting (MAP). During this period had not been done fertilization and the cultural practices were restricted to clean in form of "stripes", about 0.30 m on each side of the plants within the 1.5 m spacing named street or square and inside the spacing of 0.5 m x 0.5 m named double line. 0.90 m in the streets have been left with the herbaceous vegetation without clean or graze for future production of hay or planting of species to be joined. Precipitation data were obtained in the Agência de Águas do Estado da Paraíba – AESA. The data collection were teken in the three central lines by reading the six plants of each double line. The other, 15 plants of each double line have been left for later studies. The variables obtained in data collection were mortality of rackets-seeds, number of primary and secondary rackets per plant, primary and secondary rackets length obtained directly on the plant, primary and secondary rackets width obtained directly on the plant, weight of primary and secondary rackets and the area of primary and secondary rackets. The areas rackets were calculated by the formula AC = CC x LC x 0.693 according to Seixas et al (2014), where AC is the area of phylloclade in cm ², CC is the length of phylloclade in cm, LC is the phylloclade width in cm and 0.693 is the correction factor depending on the shape of the ellipse phylloclade.